166PThe comparison between UGT1A1 single heterozygous and wild type regarding the clinical outcomes of fixed dose irinotecan monotherapy for advanced gastric cancer: Multicenter retrospective study. (24th November 2019) - Sasaki, T; Nakano, S; Yuki, S; Sawada, K; Muranaka, T; Kawamoto, Y; Nakatsumi, H; Ando, T; Yoshita, H; Harada, K; Kobayashi, Y; Miyagishima, T; et al.
Abstract: Background: Irinotecan is a key drug for advanced gastric cancer (AGC). We previously reported that patients with UGT1A1 single heterozygous (SH) had significantly high frequency of severe hematological adverse events (AEs) compared to patients with UGT1A1 wild type (WT) in irinotecan monotherapy for AGC. However, the difference of initial dose and relative dose intensity (RDI) of irinotecan between UGT1A1 WT and SH might affect those results. Therefore, we compared between UGT1A1 SH and WT regarding the clinical outcomes of the fixed dose irinotecan monotherapy for AGC. Methods: We retrospectively analyzed the clinical data of patients who received initial fixed dose irinotecan (150mg/m2, bi-weekly) in the multi-institutional retrospective study. 100 eligible patients were registered from 8 centers in Japan. Results: The number of patients with UGT1A1 WT/SH were 62 and 38, respectively. In WT/SH patients, performance status 0/1/≥2 was 20/40/2 and 11/23/4, treatment line 2 nd /3 rd or later was 27/35 and 18/20, HER2 positive/negative 17/45 and 8/30, respectively.In WT/SH patients, median PFS was 3.15 and 3.25 months (HR = 1.137, P = 0.543) and median OS was 10.4 and 7.3 months (HR = 0.734, P = 0.184). In WT/SH patients, dose reduction of Irinotecan was required in 30.6% and 50.0% (P = 0.053), delayed treatment due to AE was observed in 44.2% and 39.4% (P = 0.675), median treatment cycle was 6 and 4 (P = 0.278), and RDI was 0.86 vs 0.86(P = 0.864), respectively. Severe hematological AEs (≥G3) were 35.4% and 63.1%(P = 0.008) and severe non-hematological AEs (≥G3) were 6.5% and 15.8% (P = 0.173), respectively. Severe AEs in more than 5% patients were leukopenia (11.3% and 15.8%), neutropenia (14.5% and 31.6%), anemia (21.0% and 23.7%), and anorexia (1.6% and 10.5%). Conclusions: UGT1A1 SH patients who received initial fixed dose Irinotecan had high frequency of severe hematological AE compared to WT patients. However, there was no significant difference in efficacy of Irinotecan monotherapy in each group. Legal entity responsible for the study: Yoshito Komatsu. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.